Sticky church - Osborne, Larry W., 1952- (Grand Rapids, Mich. : Zondervan, 2008)
There are plenty of ways to get people to come to church. Keeping them there is another matter. Many of our churches seem more like teflon than velcro. So what will it take to make your church sticky? In this book, Larry Osborne shares proven strategies for closing the back door and keeping it shut, including a unique approach to sermon-based small groups. By using these groups to dig deeper into the weekend message, Osborne's multisite congregation has grown from a small group to one of the larger churches in the country - all without any marketing. Sticky Church tells the inspiring story of North Coast Church's phenomenal word-of-mouth growth and offers practical tips for launching your own sermon-based small group ministry. This is an ideal book for church leaders who want to start or retool their small group ministry - and velcro their congregation to the Bible and each other. Includes samples of sermon notes, study questions, and leadership training materials. --from back cover.
1. Writing Great Questions -- 2. Sample Sermon Note Sheet and Study Questions -- 3. Sample Growth Group Covenant -- 4. End of the Quarter Evaluation Form -- 5. Leader Training Topics -- 6. Leader Responsibilities -- 7. Host Responsibilities -- 8. A List of the New Testament "One Anothers" -- Study Guide : Follow-up Questions for Each Chapter.
Includes bibliographical references (page 201).
Keywords: Church growth; Church group work; Small groups -- Religious aspects -- Christianity; North Coast Church (San Diego County, Calif.)